Biomarkers of the involvement of mast cells, basophils and eosinophils in asthma and allergic diseases. Issue 1 (December 2016) - Metcalfe, Dean; Pawankar, Ruby; Ackerman, Steven; Akin, Cem; Clayton, Frederic; Falcone, Franco; Gleich, Gerald; Irani, Anne-Marie; Johansson, Mats; Klion, Amy; Leiferman, Kristin; Levi-Schaffer, Francesca; et al.
Abstract Biomarkers of disease activity have come into wide use in the study of mechanisms of human disease and in clinical medicine to both diagnose and predict disease course; as well as to monitor response to therapeutic intervention. Here we review biomarkers of the involvement of mast cells, basophils, and eosinophils in human allergic inflammation. Included are surface markers of cell activation as well as specific products of these inflammatory cells that implicate specific cell types in the inflammatory process and are of possible value in clinical research as well as within decisions made in the practice of allergy-immunology.